Development of the portable device for the determination of nitrate-nitrogen contents in soil - Liu, Jun; Cai, Haotian; Pi, Jie; Zhao, Liye (International Journal of Agricultural and Biological Engineering, 2025)
Soil nitrate-nitrogen is a crucial source of plant nutrition, making the rapid, accurate, and cost-effective determination of its content highly significant for agricultural production and environmental protection. To address the limitations of traditional methods for soil nitrate-nitrogen determination, particularly the time-consuming and lab-based sample pretreatment and analysis procedures hindering on-site applications, we developed a portable soil nitrate-nitrogen determination device based on screen-printed electrodes modified with cadmium sulfide nanorods as the core components. This device incorporates mainstream embedded system technology and employs a peak-finding algorithm utilizing low-pass filtering and second-order derivatives to automatically analyze electrochemical data, enabling swift measurement of soil nitrate-nitrogen content. Performance and application tests demonstrated that this device exhibits several key features: a detection range of 0.13.0 mmol/L, a low detection limit of 0.03 mmol/L, repeatability error below 11.7%, and measurement error below 10% compared to UV spectrophotometry. The device is characterized by its rapidity, simplicity, affordability, efficiency, and adaptability, enabling swift and user-friendly on-site determination of nitrate-nitrogen content in various types and sources of soil samples, offering a practical alternative to traditional lab-based analysis. Keywords: Nitrate-nitrogen, soil, electrochemical sensor, detection DOI: 10.25165/j.ijabe.20251804.8820Citation: Liu J, Cai H T, Pi J, Zhao L Y. Development of the portable device for the determination of nitrate-nitrogen contents in soil. Int J Agric & Biol Eng, 2025; 18(4): 216–228.